Pengaruh Bentuk dan Perbedaan Kombinasi Pengikat Kayu Lamina Balau Kuning (Shorea leavis Ridl) terhadap Tingkat MoE dan MoR - Lusita Wardhani; Suriansyah Suriansyah (Jurnal Ilmu Kehutanan, 2008)
Effect of Forms and Different Combinations of the Extension of Lamina of Yellow Balau Wood (Shorea leavis Ridl) on MOE and MOR LevelsThe research aimed to find out the mechanical strength of MoE and MoR of lamina woods with different forms and combinations of the extension. Balau wood (Shorea leavis Ridl) was used as an experiment object.The research experiment was assigned based on Completely Randomized Design with two treatments and three replications. The treatments were: 4 extension types as A factor, and 4 extension fastener types as B factor. With combination of 4 x 4 x 3, the samples needed in total were 48. The Lamina’s MoE (Elasticity’s Modulus) ranged from 6.866,971 kg/cm² to 17.296,556 kg/cm² and nd the MoR (Modulus of Rupture) ranged from about 40,586 kg/cm² to 118,240 kg/cm².